Pleural Empyema due to Group D Salmonella. (29th September 2012) - Kam, Jennifer C.; Abdul-Jawad, Sami; Modi, Chintan; Abdeen, Yazan; Asslo, Fady; Doraiswamy, Vikram; DePasquale, Joseph R.; Spira, Robert S.; Baddoura, Walid; Miller, Richard A.
Abstract : Non-typhi Salmonella normally presents as a bacteremia, enterocolitis, and endovascular infection but rarely manifests as pleuropulmonary disease. We present a case of a 66-year-old female with underlying pulmonary pathology, secondary to an extensive smoking history, who presented with a left-sided pleural effusion. The causative agent was identified as being group D Salmonella . Decortication of the lung was performed and the patient was discharged on antibiotics with resolution of her symptoms. This case helps to support the inclusion of Salmonella group D as a possible etiological agent of infection in the differential causes of exudative pleural effusions.